Purification of IgY using aqueous biphasic systems composed of good’s buffers ionic liquids - Gomes, Joana Margarida Mota (2015)
The increased inefficiency of antibiotics observed in the past few years, derived from the growing number of drug-resistant organisms and the appearance of individuals with impaired immune system, led to a significant research on antibodies for use in passive immunotherapy. Antibodies obtained from the egg yolk of immunized hens, immunoglobulin Y (IgY), are a promising alternative to mammalian antibodies. They can be obtained in higher titres and by less invasive techniques, thus opening the door for a new kind of more economic biopharmaceuticals. However, the available techniques for the IgY extraction and purification are time-consuming, labor intensive, low yielding, provide low-purification levels, are of high cost and cannot easily be scaled-up for industrial applications. In this work, ABS composed of C6H5K3O7 and ILs synthetized by the combination of anions with buffer capacity (Good’s buffers), with the tetrabutylphosphonium ([P4444]+) and tetrabutylammonium ([N4444]+) cations, were investigated. The use of different ILs allowed the study of the cation and anion nature on the phase diagrams behaviour and thus on their ability to form ABS. Further, the ability of these systems as an alternative purification platform for IgY, by a selective extraction, was studied. The complete extraction and purification of IgY was not achieved in a single with the investigated ABS. However, the study of the proteins profile of the coexisting phases allowed to conclude that all proteins migrate for the top phase during the partitioning process, and that a complex between the ILs and the different proteins present in the water-soluble fraction of proteins from egg yolk was formed. Still, the results obtained reveal that the system composed of 20.1 wt % [N4444][CHES] + 16.9 wt % C6H5K3O7 is the most promising ABS for the IgY extraction.